2024
DOI: 10.3389/fpsyg.2024.1334538
|View full text |Cite
|
Sign up to set email alerts
|

The effects of demand-resource relationship on work-family conflict under Chinese culture: a cross-sectional study

Tianjiao Li,
Zhiwei Helian,
Ling Hu
et al.

Abstract: Chinese work and lifestyle are undergoing dramatic changes caused by constantly changing technology and new policies. The demand-resource dynamic relationship, which leads to work-family conflict (WFC), has become increasingly complicated. However, very little is known about the combined effects of different factors from work and family spheres on WFC. This study aims to explore (1) the discrepancy between fit and misfit, (2) the discrepancy of the different degrees of fit, and (3) the discrepancy of the diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…For instance, Oren and Levin (2017) found that individuals who reported a higher threat of loss of resources reported experiencing higher work–family conflict than those who reported resource enrichment. Moreover, reports of previous studies (e.g., Pak et al, 2022 ; Brandão and Matias, 2024 ; Dishon-Berkovits et al, 2024 ; Li et al, 2024 ) have consistently shown that personal and job resources are important in reducing work–family conflict and depletion of such resources lead to the experience of work–family conflict. In sum, the COR and W-HR views suggest that work engagement is positively related to work–family conflict because work engagement involves resource investment during work (e.g., time, energy) and the individual is left with depleted resources and unable to effectively perform family roles after work.…”
Section: Introductionmentioning
confidence: 90%
“…For instance, Oren and Levin (2017) found that individuals who reported a higher threat of loss of resources reported experiencing higher work–family conflict than those who reported resource enrichment. Moreover, reports of previous studies (e.g., Pak et al, 2022 ; Brandão and Matias, 2024 ; Dishon-Berkovits et al, 2024 ; Li et al, 2024 ) have consistently shown that personal and job resources are important in reducing work–family conflict and depletion of such resources lead to the experience of work–family conflict. In sum, the COR and W-HR views suggest that work engagement is positively related to work–family conflict because work engagement involves resource investment during work (e.g., time, energy) and the individual is left with depleted resources and unable to effectively perform family roles after work.…”
Section: Introductionmentioning
confidence: 90%